Sufism and Islamic Moderation in the Digital Era: The Relevance of KH. Said Aqil Siroj’s Thought in Sustainable Character Education - ‘Athiyyah, Avita Aniqotul; Mashabi, M. Ali (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Said Aqil Siroj’s thought on Sufism as the foundation of moderate Islam offers a substantive contribution to strengthening sustainable Islamic character education in the digital era. This study explores KH. Said Aqil Siroj’s conceptualization of Sufism-based moderation, the role of Sufism in cultivating inclusive and tolerant attitudes, and the impact of his thought on multicultural society. The research employs a descriptive approach through qualitative analysis using the library research method. The data analysis techniques include data reading, data presentation, and conclusion drawing. The findings of this study show that: 1) KH. Said Aqil Siroj emphasizes tolerance, ukhuwah imaniyyah (spiritual brotherhood), and interfaith solidarity. His perspective highlights social harmony, respect for differences, and the nurturing of unity in diversity to create a peaceful Indonesia. 2) KH. Said Aqil Siroj underscores the importance of Sufism in teaching tolerance, interreligious dialogue, and moral development. His teachings help Muslims confront radicalism and foster an inclusive society. 3) KH. Said Aqil Siroj’s thought on Sufism promotes harmony and influences government and educational policies that support tolerance and pluralism. So that Sufism can become an impactful educational paradigm that integrates spiritual, social, and sustainable values. This study contributes a novel perspective by positioning Sufism as a model of sustainability-oriented character education in the digital era, bridging Islamic moderation discourse with global discussions on digital ethics, religious pluralism, and character formation in technologically mediated societies.